Lactococcus lactis, an alternative system for functional expression of peripheral and intrinsic Arabidopsis membrane proteins. - Annie Frelet-Barrand (Public Library of Science (PLoS), 2010)
Background Despite their functional and biotechnological importance, the study of membrane proteins remains difficult due to their hydrophobicity and their low natural abundance in cells. Furthermore, into established heterologous systems, these proteins are frequently only produced at very low levels, toxic and mis- or unfolded. Lactococcus lactis, a gram-positive lactic bacterium, has been traditionally used in food fermentations. This expression system is also widely used in biotechnology for large-scale production of heterologous proteins. Various expression vectors, based either on constitutive or inducible promoters, are available for this system. While previously used to produce bacterial and eukaryotic membrane proteins, the ability of this system to produce plant membrane proteins was until now not tested. Methodology/principal findings The aim of this work was to test the expression, in Lactococcus lactis, of either peripheral or intrinsic Arabidopsis membrane proteins that could not be produced, or in too low amount, using more classical heterologous expression systems. In an effort to easily transfer genes from Gateway-based Arabidopsis cDNA libraries to the L. lactis expression vector pNZ8148, we first established a cloning strategy compatible with Gateway entry vectors. Interestingly, the six tested Arabidopsis membrane proteins could be produced, in Lactococcus lactis, at levels compatible with further biochemical analyses. We then successfully developed solubilization and purification processes for three of these proteins. Finally, we questioned the functionality of a peripheral and an intrinsic membrane protein, and demonstrated that both proteins were active when produced in this system. Conclusions/significance Altogether, these data suggest that Lactococcus lactis might be an attractive system for the efficient and functional production of difficult plant membrane proteins.